Iowa Birdline update, October 29, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Iowa Birdline update for October 29, 1990. Highlights of the update include sightings of a Pacific Loon, a Prairie Falcon, and a Northern Goshawk. Other interesting observations were of numerous species of Grebes and all 3 species of Scoters. Epson - sheet feed/flatbed